Improving Financial Technology-Based Financial Behavior Capabilities in Jayapura City and Jayapura Regency MSMEs - Pascalina V. S Sesa; Maylen K. P Kambuaya; Rudiawie Larasati; Klara Wonar (Journal of The Community Development in Asia, 2025)
This study assesses how financial technology (fintech) has helped MSMEs in Jayapura City and Jayapura Regency improve their financial behavior. This study used a quantitative methodology with associative and moderation techniques to gather data via questionnaires, which WarpPLS was then used to analyze. The study's findings demonstrate that financial behavior, which aids in cash flow management and guards against mistakes that could result in bankruptcy, is significantly influenced by financial literacy. Furthermore, MSME entrepreneurs' good financial behavior is positively influenced by personality traits like thoroughness and openness, particularly regarding capital management and investment decisions. Fintech, however, cannot moderate the relationship between financial behavior and financial literacy because these digital tools cannot close the knowledge gaps in finance that must be addressed to make wise financial decisions. Similarly, personality traits like neuroticism and extroversion influence an individual's financial behavior more than technology use. Therefore, fintech cannot moderate the association between financial personality and behavior. These results can guide local governments and universities in offering financial management and digital training to MSME actors, boosting regional financial inclusion